The right to be a child enriching the Bahay Pag-asa through hierarchical optimization - Clemente, Jeremy William Y. (College of Architecture, University of the Philippines Diliman, 2025)
Architecture’s physiological and psychological effects on humans underscore the importance of good design. Children In-Conflict with Law represents a subset of the population whose restricted liberty confines them to a single building over a prolonged period. Despite the existence of regulatory standards on the development of Bahay Pag-Asa, there are still gaps in its architectural implementation. Specifically, there is a lack of spatial diversity and specifications catering to its target age group. This project aims to bridge these gaps by taking a holistic approach through which the existing standards are expounded on and made conducive to human development. Qualitative analysis performed on related literature and interviews with experts and Bahay Pag-Asa staff reconciled theory with reality of the typology. A co-design approach with a multidisciplinary team reinforced the iterative process of the design development phase. The project output is envisioned to transform the youth detention center into a development conducive environment built on the principles of Normative Design. It provides a complete suite of spaces coherently woven into a microcosm of our built environment. Architectural solutions were thereafter compiled into a manual for reference. In conclusion, this proposal utilized architecture to support the continuous human development of Children In-Conflict with the Law as they contend with deprivation of liberty.